OC-071 Epithelial cytoplasmic hmgb1, epithelial nuclear runx3 and dynamic stromal lymphocytic phenotype are associated with oesophageal neoplastic progression. (17th June 2017) - Porter, RJ; Brice, DP; Murray, GI; Petty, RD; McLean, M
Abstract : Introduction: Barrett's oesophagus (BO) defined by metaplastic columnar epithelium in the distal oesophagus is a pre-malignant lesion for oesophageal adenocarcinoma (OAC). HMGB1 impacts genomic stability, influences epithelial cell behaviour and immune response. We previously reported loss of nuclear and emergence of cytoplasmic epithelial HMGB1 in BO and dysplasia. Our aim was to define expression of HMGB1 in upper GI malignancy, assess expression of HMGB1 downstream effector proteins p53 and RUNX3 and characterise lymphocytic infiltrate in oesophageal neoplastic progression. Method: Tissue was sourced from the Grampian Biorepository (n=241 total). Intensity of epithelial nuclear and cytoplasmic expression of target proteins were assessed immunohistochemically in a tissue microarray representing 150 upper gastrointestinal cancers (58 OAC, 9 oesophageal squamous cancer, 83 gastric adenocarcinoma), 15 normal oesophageal mucosa, 24 normal gastric mucosa and 14 BO mucosa adjacent to OAC. Expression of p53, RUNX3 and lymphocytic inflammatory cell infiltrate was also assessed in 78 and 13 biopsies from 19 and 10 patients with non-dysplastic or dysplastic BO. Data was analysed by relative frequencies of staining correlated to clinico-pathological data, Fisher's exact test and Mann-Whitney U test. Results: There was loss of nuclear HMGB1 across all cancer phenotypes. Epithelial cytoplasmic HMGB1 expression was associated with OAC compared to normal epithelium (p<0.001), albeit with weaker intensity to non-dysplastic (p=0.001) or dysplastic BO (p=0.002). In gastric adenocarcinoma, a strong cytoplasmic HMGB1 (p=0.010) and strong nuclear p53 (p=0.033) was associated with improved survival. Dysplastic BO expressed strong nuclear p53 as expected (p<0.001 compared to normal mucosa) and this was lost on malignant transformation (p<0.001). Epithelial nuclear RUNX3 was associated with dysplastic BO (p=0.004). A robust RUNX3 positive lymphocytic stromal inflammatory infiltrate was seen in BO. Immunophenotyping revealed that dysplastic BO is associated with increased Foxp3 + regulatory T cells (p<0.002) and non-dysplastic BO with reduced CD20 + B cell (p<0.001), CD4 + (p<0.001) and CD8 + (p<0.001) T cell subset infiltration. Conclusion: This study offers new insight into the pathogenesis of oesophageal neoplastic progression. The biological significance of dynamic localisation and intensity of HMGB1 and RUNX3, and changes in adjacent stromal inflammatory cell infiltrate warrant further investigation to determine a protective or pathogenic role in oesophageal neoplasia. Disclosure of Interest: None Declared